Use of Direct Oral Anticoagulants in Children and Adolescents - Albisetti, Manuela (Hämostaseologie, 2020)
While the need for anticoagulation in children has increased over the last decades, dose regimens of currently used anticoagulants, including low-molecular-weight heparin (LMWH) and vitamin K antagonist (VKA), are still extrapolated from adult guidelines because well-designed clinical trials were never performed in children. This approach is not optimal due to specific pediatric features of the hemostatic system and pathophysiology of thrombosis. These anticoagulants also present several disadvantages that further hamper optimal anticoagulation of pediatric patients, especially newborns and infants. The new direct oral anticoagulants (DOACs), which have the potential to overcome these disadvantages, were extensively investigated in adults and have become a valid alternative to LMWH and VKA for anticoagulation in the adult population. Several pediatric trials on all approved DOACs are currently ongoing, providing specific pediatric formulations and age- and weight-adjusted dose guidelines. First results of phase III trials indicate that DOACs are at least as efficient and safe as LMWH and VKA for the treatment and prevention of thrombotic events in children with different clinical conditions. This review article summarizes available data from terminated and ongoing controlled trials on DOACs in children and adolescents.
Keywords: direct oral anticoagulants; anticoagulation; children; thrombosis